Pomegranate protects renal proximal tubules during gentamicin induced-nephrotoxicity in rats - Alkuraishy, Hayder M.; Al-Gareeb, Ali I.; Al-Naimi, Marwa Salih (Journal of Contemporary Medical Sciences, 2019)
Objective: The aim of present study was to evaluate the nephroprotective effect of pomegranate in gentamicin induced-nephrotoxicity in rats. Methods: Thirty Sprague Dawley Male rat were used, which randomly divided into 3 groups, 10 rats in each group. Group1 (n=10): Rats treated with distilled water for 12 days.Group2 (n=10): Rats treated with distilled water + Gentamicin .Group3 (n=10): Rats treated with pomegranate + gentamicin. Blood urea, serum creatinine, serum malondialdehde (MDA), superoxide dismutase (SOD) , glutathione reductase (GSH) , Neutrophil Gelatinase Associated Lipocalin (NGAL) , kidney injury molecules (KIM-1) and Cystatin-c were measured . Results: Blood urea and serum creatinine were significantly elevated in gentamicin group compared to the control p=0.007 and p=0.04 respectively. Also estimated GFR was significantly decreased in gentamicin group compared to the control p=0.04. Cystatin-c serum level and MDA serum level were increased but SOD and GSH were decreased insignificantly in gentamicin group compared to the control p>0.05. Pomegranate reduced blood urea significantly p=0.002. Pomegranate improves endogenous anti-oxidant capacity since; it increase GSH significantly compared to gentamicin group p=0.02. There were insignificant effects on MDA and SOD. Moreover, pomegranate reduce serum levels of KIM-1and NGAL in gentamicin group p<0.05. Conclusion: Pomegranate attenuates gentamicin induced-nephrotoxicity through potentiation of endogenous anti-oxidant capacity and inhibition of inflammatory pathway.